Impact of implementing a vancomycin protocol to reduce kidney toxicity: A comparative study - Baiocco, Graziella Gasparotto; Greiner, Stephanie; Rosa, Mário Borges; Flores, Cecília Dias; Barros, Helena M. T. (Frontiers in Pharmacology, 2023)
Introduction: Vancomycin is a frequently used for treating severe infections caused by multidrug-resistant, gram-positive pathogens. To ensure its effectiveness and minimize the risk of nephrotoxicity, safe administration and dose monitoring are crucial. Understanding the impact of vancomycin serum levels on clinical outcomes is of paramount importance, necessitating improved knowledge on its use, dose monitoring, nephrotoxicity, Objective: Aimed to evaluate the incidence of Acute Kidney Injury (AKI) in patients receiving vancomycin before and after the implementation of an institutional protocol for vancomycin administration in a public tertiary hospital in southern Brazil. Materials and methods: A cross-sectional study design was employed, analyzing data from the electronic medical records of 422 patients who received vancomycin. The patient population was divided into two independent cohorts: those treated in 2016 (pre-protocol) and those treated in 2018 (post-protocol), following the implementation of the institutional vancomycin administration protocol. Results: Included 211 patients in each year of assessment. Patients from both cohorts had a Charlson Comorbidity Index (CCI) score of 4. Post-protocol cohort consisted of older individuals, with a mean age of 62.8 years. Additionally, patients in the post-protocol year had higher baseline creatinine levels, higher rates of Intensive Care Unit (ICU) hospitalization, and increased use of vasopressors. In the pre-protocol year, patients received vancomycin therapy for a longer duration. When comparing the incidence of AKI between the two groups, an intervention study revealed rates of 38.4% in group 1 and 20.9% in group 2, indicating a significant reduction (p < 0.001) in the post-protocol group. A logistic regression model was developed to predict AKI, incorporating variables that demonstrated significance (p ≤ 0.250) in bivariate analysis and those recognized in the literature as important factors for AKI, such as duration of therapy, vancomycin serum level, and ICU hospitalization and classification performance was assessed using a receiver operating characteristic (ROC) curve, yielding an area under the curve of 0.764, signifying acceptable discrimination of the regression model. Conclusion: Implementation of the institutional protocol for vancomycin administration resulted in a significant and cost-effective impact, ensuring appropriate therapeutic dosing, reducing adverse events and improving clinical outcomes for patients in the study population.